2022
DOI: 10.1016/j.jhep.2021.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Patient pIgR-enriched extracellular vesicles drive cancer stemness, tumorigenesis and metastasis in hepatocellular carcinoma

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…Nowadays, the roles of aberrant PIGR in tumors remain controversial, which might be due to the tumor heterogeneity or the different underlying mechanisms. In hepatocellular carcinoma, PIGR-loaded extracellular vesicles could activate Akt/GSK3 β / β -catenin signaling cascades, driving cancer stemness, tumorigenesis, and metastasis [ 35 ]. Ohkuma et al have assessed the prognostic value of PIGR in pancreatic cancer patients after surgical resection and determined that the overexpression of PIGR was correlated with poor prognosis in pancreatic cancer [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, the roles of aberrant PIGR in tumors remain controversial, which might be due to the tumor heterogeneity or the different underlying mechanisms. In hepatocellular carcinoma, PIGR-loaded extracellular vesicles could activate Akt/GSK3 β / β -catenin signaling cascades, driving cancer stemness, tumorigenesis, and metastasis [ 35 ]. Ohkuma et al have assessed the prognostic value of PIGR in pancreatic cancer patients after surgical resection and determined that the overexpression of PIGR was correlated with poor prognosis in pancreatic cancer [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The level of pIgR in circulating sEVs was reduced in a majority of patients after surgical resection. 24 The studies underscore the potential of those sEV proteins as diagnostic and prognostic markers of HCC. The translation of the research findings to clinical application of these sEV proteins requires further validation of their expression in a large cohort of patients.…”
Section: Potential Role Of Sevs As Biomarkers Of Hcc Diagnosis and Tr...mentioning
confidence: 97%
“…Polymeric immunoglobulin receptor (pIgR)-enriched sEVs collected from patients with advanced HCC have been reported to promote cancer stemness, tumorigenesis, and metastasis of HCC, by a mechanism that involved an EV-pIgR-activated PDK1/Akt/GSK3β/β-catenin signaling cascade. 24 Using anti-pIgR antibody, the study showed that blockade of EV-pIgR-mediated intercellular communication in tumor microenvironment might provide a new therapeutic strategy for cancer patients. Rab GTPases are involved in the biogenesis of exosomes.…”
Section: Effects Of Sevs On the Cancerous Properties Of Hccmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the findings presented by Tey et al 7 pinpointed the prominent role of PIGR-enriched EVs as key players in HCC aggressiveness and as a promising therapeutic target. In fact, PIGR has been linked to malignant transformation of epithelial cells for the last 5 decades.…”
mentioning
confidence: 88%